PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATERI KELARUTAN DAN HASIL KALI KELARUTAN KELAS XI IPA MAN 2 PONTIANAK - Lili Suryani; Hairida Hairida; Dini Hadiarti (Jurnal Ilmiah Ar-Razi, 2017)
ABSTRACTThis result aimed to determine the differences activities and student's learning result by using the model of problem and speech method on solubility and the result of multiplying the solubility material in science class of XI MAN 2 Pontianak. Formulation on this research used an experiment method. The results showed that 1) There were some influences of PBL model to student activities at Solubility and Solubility Product in the class of XI MAN 2 Pontianak. 2) There were some influences of PBL model to student learning results in solubility material in the class. 3) The influence of PBL model to student activities at Solubility and Solubility Product in class of XI MAN 2 Pontianak was 95%. 4) The influence of PBL model on student learning results at Solubility and Solubility Product in class of XI MAN 2 Pontianak was 95%.Keywords: Activities, Learning results, Problem Based Learning